Dietary Supplementation of Fructooligosaccharides Enhanced Antioxidant Activity and Cellular Immune Response in Broiler Chickens - Al-Surrayai, Tahani; Al-Khalaifah, Hanan (Frontiers in Veterinary Science, 2022)
This study investigated the impact of various concentrations of fructooligosaccharides (FOS) prebiotic on the production performance, antioxidant status, and immune response of broiler chicken. The FOS was used at 0, 0.3, 0.5, and 0.7%. The cycle included 340 broilers distributed into 4 batteries, with 85 broiler chickens in each battery. There were 5 replicates with 17 broiler chickens each, and the analyses were triplicated. The studied parameters were production performance, antioxidant status, hematological measurements, cellular and humoral immune response, intestinal acidosis, intestinal microbial counts, and volatile fatty acid (VFA) level in the hindgut. Results showed that broiler chickens fed 0.7% of FOS had significantly higher body weight gain than the control group and the groups fed 0.3% and 0.5% of FOS. Supplementing broiler feed with FOS at all levels increased the total antioxidant capacity (TAC) and reduced the malondialdehyde of the sera (P = 0.015 and 0.025, respectively). Liver catalase enzyme in the broiler chickens fed 0.5 and 0.7% of FOS was higher than that of the control group and the group fed 0.3% of FOS (P = 0.001). However, the liver MDA of the control group was higher than that of all the other groups (P = 0.031). The total WBC and heterophils % were the highest after supplementing broilers with 0.7% FOS (P = 0.004 and 0.003, respectively) at 3 wks of age. Conversely, lymphocytes and monocytes were the lowest for the 0.7% FOS group (P = 0.030 and 0.020, respectively). Dietary 0.05 and 0.7% of FOS induced the highest cellular response compared to the other treatments (P = 0.020). Thymus, bursa of Fabricious, and spleen weights were enhanced after FOS supplementation, which indicates a higher specific cellular response. To conclude, FOS prebiotic at all levels can be utilized safely to enhance the antioxidant activity and the cellular immune response of broiler chickens. Using 0.7% of FOS resulted in higher body weight of broilers. Accordingly, this amount of FOS is sufficient to reach the required results.